Visual Semiotics Analysis on Television Ads UHT Ultra Milk “Love Life, Love Milk” - Peter Ardhianto; William Manuel Son (International Journal of Visual and Performing Arts, 2019)
The number of adverts that have sprung up this digital era has made the creative industry try to break new breakthroughs so that advertisements can be more able to get the attention of the audience by making many innovations. As in the uht ultra love life love milk television television ad. What is applied to television advertising media that has a general target for all people who see this ad, and the main target is young people because it is more relevant and consumers are mostly young people, because milk supports the development period. The purpose of this study is to help review the meaning of a modern advertisement, especially milk advertisements which are usually for children but aimed at all ages.This study uses Roland Barthes's semiotic theory as a theory in the study of television ads, with methods of documentation, interviews, literature studies, so that the right data is collected to be analyzed. So the conclusion in this study is that uht ultra love live love milk television advertising has the message contained in each video scene that is combined with verbal text emphasis and changes in typographic elements that have their own meaning to trigger emotions from consumers.